Efficacy of Bee Venom as an Anti-Viral Therapy for HCV Genotype 4 (Global Journal of Medical Research, 2014)
Use of traditional medicine is encouraged in many economically diverse countries when conventional medications fail. HCV prevalence is highest in Egypt at >10% of the general population, and China has the most people with HCV (29.8 million); approximately 52% of patients infected with HCV genotype 4 will develop chronic HCV. The use of interferon, currently the only approved therapy, is frustrating in many situations. Use of camel milk or drinking copious amounts of urine, moxibustion by fire, acupuncture and cupping, especially in the Saharan and Arabian areas, is currently popular in Egypt. Some traditional Egyptian medicine is related to Arabian, ancient Egyptian, or other religious beliefs. Most patients using traditional therapies show improvement over time in both clinical symptoms and laboratory results. Some showed SVR using Bee venom therapy.
Keywords: bee venom; HCV; traditional; therapy